VILLA ISOLA SEBAGAI OBJEK DAYA TARIK WISATADALAM UPAYA PELESTARIAN BENDA CAGAR BUDAYA - Adinda Cikal Gita Martha, - (2009)
Bandung is one of the city that has a very long history. In the course of its history, the city of Bandung left some buildings of historical value, as one of the evidence (the source of artifacts) from the existence and prosperity of the city in the past. Gradually in the city of Bandung stood stately buildings and modern until the amount is more than 50 buildings. Now the historic building that should have stayed awake more and more reduced. Villa Isola as one of the assets of Indonesia requires that sufficient attention in its conservation efforts, although the sustainability awake enough for the current function is as an office of Rector of UPI, but better still if the Villa Isola can be utilized so that the preservation can be sustainable. This can be done from the tourism potential given by the Villa Isola and will provide value if developed as an object of tourist attraction. In this study, the author uses descriptive method of analysis of research methods aimed at solving problems faced today, then the data is collected, compiled, described, and analyzed by describing a condition that occurs in the present and explain each variable studied. After that the processing of data using a SWOT analysis (strength, weakness, opportunities, threat). To preserve Villa Isola revitalization efforts are working in reviving the area that used to live. The efforts are returning back to form and function of Villa Isola is now used as the Rector's office. Villa Isola has more potential to be developed as an object of attraction is suitable Isola wisata.Villa if developed as a museum,. After outlining the potential - the potential of Villa Isola, then the author will do zoning. After zoning, and recreational activities will be determined that can be done at Villa Isola.